2003
DOI: 10.1002/art.11016
|View full text |Cite
|
Sign up to set email alerts
|

Sex effect on clinical and immunologic quantitative trait loci in a murine model of rheumatoid arthritis

Abstract: Objective. To explore the effect of sex on clinical and immunologic traits in major histocompatibility complex-matched (H-2d) F 2 hybrid mice with proteoglycan (PG)-induced arthritis and to identify how the quantitative trait locus (QTL) on the X chromosome influences the onset QTL of another chromosome.Methods. (BALB/c ؋ DBA/2)F 2 hybrid mice were immunized with cartilage PG, and a genome-wide linkage analysis was performed using >200 simple sequence-length polymorphic markers. The major clinical traits (susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 64 publications
2
60
0
1
Order By: Relevance
“…It is the first PIA susceptibility QTL described to date in the mouse and it colocalizes with QTL described for other models of RA, namely Cia5 21 and Pgia26. 22 Recently, evidence was reported for the existence of three QTLs in the Cia5 region. 23 At this time, results do not allow us to conclude that the QTL detected in the present experiment results from the effect of a single gene or the combined effect of multiple genes, as it seems to occur at the Cia5 region, where it has been recently reported that a cluster of genes are differentially expressed during CIA 24 and it will be interesting to investigate if the same occurs in the PIA model.…”
Section: Discussionmentioning
confidence: 99%
“…It is the first PIA susceptibility QTL described to date in the mouse and it colocalizes with QTL described for other models of RA, namely Cia5 21 and Pgia26. 22 Recently, evidence was reported for the existence of three QTLs in the Cia5 region. 23 At this time, results do not allow us to conclude that the QTL detected in the present experiment results from the effect of a single gene or the combined effect of multiple genes, as it seems to occur at the Cia5 region, where it has been recently reported that a cluster of genes are differentially expressed during CIA 24 and it will be interesting to investigate if the same occurs in the PIA model.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in rodent intercrosses identified several arthritis susceptibility, severity and chronicity loci (Table 1). 29,[32][33][34][35][36][37][38][39][40][41][42][43][44][45] The RA genome-wide family-based genetic studies were not designed or structured to address disease severity, histologic damage or the other arthritis-related phenotypes that can be studied in rodents. More recent cohorts have been incorporating severity and outcome parameters in their prospective data collection and will likely have a major role in RA severity genetic association studies.…”
Section: Inducible Modelsmentioning
confidence: 99%
“…24 Similar gender specific effects have been detected in rat and mouse intercrosses or congenic strains. 33,57,80 Sex chromosomes have also been implicated in the regulation of autoimmune arthritis. The Yaa locus in mice unexpectedly reduced CIA severity.…”
Section: Gender-gene Interactionsmentioning
confidence: 99%
“…Based on previous observations that certain loci operate in a gender-specific manner, 12,14,15 males and females were first studied separately and then in combined analyses.…”
Section: Induction Of Collagen-induced Arthritismentioning
confidence: 99%
“…11 Additionally, yet unidentified sex factors appear to regulate the penetrance of certain arthritis-regulatory alleles, making some disease alleles sex-specific. [12][13][14][15][16][17] Little is known about the genetic regulation of disease severity and none of the RA multi-institutional familybased genome-wide screens was designed to address disease severity. These severity genes could have a more significant role in the perpetuation (chronicity) of the inflammatory process and joint damage, and thus could generate better targets for drug development.…”
Section: Introductionmentioning
confidence: 99%